Recommendations and child care in context COVID-19 - Larraguibel Q., Marcela; Astudillo G., Rodrigo (Revista de Psiquiatría Clínica, 2022)
The pandemic and confinement can have adverse consequences on the mental health of children and adolescents (NNA). In them, concerns appear that lead to regressive behaviors, somatic symptoms, irritability, separation anxiety, behavioral problems, withdrawal, sleeping difficulties, and changes in appetite. Special attention should be paid to the vulnerable population of children and adolescents and to the prevention of abuse. This article reviews the impact of quarantine on the mental health of children and adolescents and proposes recommendations to reduce the psychological consequences of confinement.